Equilibrium and Disequilibrium Exchange Rate: Case of Rupiah Exchange Rate - Santosa, Agus Budi (International Journal of Economics and Financial Issues, 2017)
This article would analyze the determination of Rupiah exchange rate by using equilibrium and disequilibrium concepts. This analysis became important for policy maker because disequilibrium reflected distortion towards relative price related to domestic policies. The research results showed that Rupiah exchange rate was in disequilibrium condition. The conclusion was based on Indonesia Bank policies that conducted intervention through some regulations by emerging Indonesia Bank regulations and conducting intervention on foreign exchange market, both in demand and supply. The Indonesia Bank policies aimed to stabilize Rupiah exchange rate that led to equilibrium exchange rate. The research results also showed Purchasing Power Parity did not applied in short term. It indicated market inefficiency and led to price rigidity in commodity market. The price rigidity caused price adjustment did not work. As a result, market was in disequilibrium condition. Keywords: Equilibrium, Disequilibrium, Intervention, Purchasing Power Parity, Price Rigidity JEL Classification: F310